Depression as a Manifestation of Obstructive Sleep Apnea - Shoib, Sheikh (J Neurosci Rural Pract, 2017)
BACKGROUND: Obstructive sleep apnea (OSA) often results in a wide range of comorbid conditions, predominantly of the cardiovascular/respiratory, endocrine/metabolic, and neuropsychiatric symptoms. In view of the ambiguity of literature regarding the association between OSA and depression, we conducted this study to show any association between the two disorders. OBJECTIVE: The aim of the study was to see the association between OSA and depression and to study the prevalence of OSA in patients suffering from depression. METHODS: We performed polysomnography (PSG) studies of patients that were referred from various subspecialty clinics from July 2011 to August 2013. Psychiatric diagnosis was done using mini international neuropsychiatric interview plus scale. This was followed by application of Hamilton Depression Rating Scale (HAM-D). Standard methods of statistical analysis were used for data analysis. RESULTS: Out of 182 patients who underwent PSG, 47 were suffering from depression with a mean age significantly more (P < 0.001) than that of other population (58.60 years vs. 53.60 years). In our 47 depressed patients, 44 (93.6%) had abnormal PSG. Based on apnea-hypopnea index score, 3 (6.8%) patients had mild, 18 (40.9%) had moderate, and 23 (52.3%) had severe OSA. The mean HAM-D score was significantly more in depression patients, (17. 35 ± 5.45) as compared to non depressive patents (8.64 ± 6.24) (P = 0.0001). CONCLUSION: This study demonstrates significant overlap between the sleep apnea and depression. Health specialists need more information about screening for patients with OSA to ensure proper diagnosis and treatment of those with the condition. Most of the clinicians do not suspect this important comorbidity of depression in the beginning resulting in delayed diagnosis.